Community‐engaged Research Approaches: Multiple Pathways To Health Equity. Issue 3 (26th July 2021) - Haapanen, Krista A.; Christens, Brian D.
Highlights: Popular models and unifying frameworks fail to capture variance in community‐engaged research (CEnR) CEnR projects vary in how they approach process and partnership, knowledge generation, and power An expanded taxonomy of community‐engaged research could cultivate new approaches to social change